ANALISIS HUKUM TERHADAP PELAKSANAAN TANGGUNG JAWAB NAHKODA TERHADAP KESELAMATAN PENUMPANG: LEGAL ANALYSIS OF THE IMPLEMENTATION OF THE SKILDER'S RESPONSIBILITY FOR PASSENGER SAFETY - Tamzilal Padhamara, Jesica Khofifah; Kamsilaniah; Juliati (Faculty Of Law Bosowa University, 2021)
This research was conducted aiming to find out the steps taken by the captain in meeting passenger safety standards and how the form of responsibility given by PT. Pelni in providing services that meet passenger eligibility standards. The research was conducted at the PT. Pelni Makassar Branch office and the research method used was an empirical normative research type that combines the implementation of the Act in its application in people's lives through interviews and documentation. The results showed: 1) the steps taken by the captain in meeting safety standards for passengers where the captain as the highest leader on the ship who was responsible for the comfort, safety and security for passengers was carried out together with the harbormaster by supervising the ship and checking the ship's documents before do the voyage so as not to experience excess passenger capacity. 2) The form of responsibility carried out by the PT. Pelni Makassar Branch Office as a party to the implementation of sea transportation makes it the responsibility of the carrier for the safety and security as well as the feasibility of the passengers and/or goods being transported by ensuring that all facilities on board the ship are in accordance with the provisions laid down. applies then arranges for ship passengers to board the correct ship and passengers enter the ship regularly and assist passengers who have difficulty boarding the ship after all passengers have boarded the ship the number of passenger tickets is confirmed by the port inspector using turnstile meters or computer systems. Theanumber of passengers mustabe submitted to the Master when theaship is en route.